Джерела дослідження святкової культури Миколаївщини кінця XIX – початку XX ст. - Мицик, С.В. (Культура народов Причерноморья, 2013)
У статті автор робить спробу комплексно дослідити та систематизувати джерельну базу
святкової культури Миколаївщини кінця ХІХ – початку ХХ ст. Зосереджує увагу на феномені святкової
культури та подає систематизовану джерельну базу на основі двох міждисциплінарних підходів:
етнографічно-фольклористичному підході кінця ХІХ – першої половини ХХ ст. та мистецтвознавчо-
культурологічному. Основну джерельну базу дослідження святкової культури Миколаївщини кінця ХІХ –
початку ХХ ст., яка складається з документів архівних та музейних фондів, матеріалів періодичної
преси дослідженого періоду, формує в 4 групи. В статье автор делает попытку комплексно исследовать и систематизировать базу
источников по изучению праздничной культуры Николаевщины конца XIX – начала ХХ века.
Концентрирует внимание на феномене праздничной культуры и систематизирует базу источников на
основе двух междисциплинарных подходов: этнографическо-фольклористическом подходе конца XIX –
первой половины ХХ в. и искусствоведческо-культурологическом. Основную базу исследования
праздничной культуры Николаевщины конца XIX – начала ХХ в., которая состоит из документов
архивных и музейных фондов, материалов периодической печати исследуемого периода, формирует в 4
группы. The authors attracts attentions to the festive culture phenomenon of Mykolaevshina in the period of
the end of the XIX – the beginning of XX age and makes an attempt to investigate and to systematize the sources
for studying this phenomenon investigating the festive culture, the authors systematize the base of sources on the
basis of two disciplinary approaches: ethnographical-folklore in the period of the end XIX – the first half of XX
age, in which accents attention to the researches of M. Arkas, S. Tsvetko, H. Bakhmann, V. Zhermuntskiy,
K. Keller, A. Velitsin, D. Bagaliy, A. Klaus, A. Skalkovskiy and others.
The works of these organic supplements of collection of newsper’s periodicals, of sources/ iv the second
approach – study of art-culture and culturological, authors gives consideration to works of A. Kurochkin,
N. Gogokhiy, T. Gaevskaya, S. Besklubenko, A. Lymanskiy, A. Pankov and others.
The authors marks out the regional aspects of the festive culture development of Mykolayiv region, which are
represented in the works of Drizo-Omelyanenko, A. Shpachinskiy, A. Zaturyan, A. Makarenko, O. Kovaleva,
V. Belov and in the writings of authors collectives under the direct of M. Shytyuk, V. Drizo-Omelyanenko.
The principal base of festive culture of Mykolaivschina in the period of the end of the XIX – the beginning of XX
age, which consists of archives’ documents and museums funds, materials of periodical of researched period is
formed into 4 groups. The first group is documentation of the State Archives of Mykolaiv region of the prerevolutionary
period. The second group is museums’ funds of Mykolaiv region, and the third group is the private
archives of musical and theatrical art works of Mykolaiv, their memoirs, journals. The fourth group consists of
periodicals of past and the present.